Disfunción familiar y Depresión postparto en mujeres atendidas en el servicio de ginecobstetricia del Hospital Isidro Ayora, en el periodo 2021 – 2022 - Paredes Bravo, Emily Camila (2022)
The postpartum family plays a fundamental role by providing comfort to the mother and the newborn, being emotional and socioeconomic support, promoting recreation, among other needs. This is where family functionality becomes important, since the recent mother, perceiving a functional family, could feel emotionally stable; however, if the family is dysfunctional, the risk of developing depressive symptoms may or may not increase. With this background, the present investigation had as objectives: to determine the relationship between family dysfunction and postpartum depression; identify and measure levels of family dysfunction and postpartum depression; and design a psychological prevention proposal for those mothers who present family dysfunction and postpartum depression. The study was crosssectional, non-experimental and quantitative, with a descriptive and correlational scope. The Family Perception Questionnaire and the Edinburgh Postpartum Depression Scale were applied, taking 113 puerperal women as a sample. Among the results, it is evident that the minority of participants present family dysfunction and most suffer from postpartum depression; concluding that there is no significant relationship between both study variables